Suitability of flood early warning system in Pergau River, Kuala Balah - Mustaffa, Ahmad Mukrim (2018)
Flood has become an annual event in the area of east Peninsular Malaysia due to heavy rainfall during monsoon season. Although it happens every year, the effects caused by ﬂood cannot be reduced and it remains an inordinate threat to people since ﬂood mitigation and ﬂood vulnerability methods apply is not comprehensive. Therefore, early warning system is needed in order to overcome and reduce the potential losses in the future. The ﬂood phenomenon occur will leads to a tremendous effects in terms of social, economic and environmental degradation. Recently in the year 2014, Kelantan again experienced massive ﬂood that almost the same as the previous record in 1967 in terms of scale and intensity. Thus, this study was conducted to identify the suitable ﬂood early warning systems at Pergau River, Kuala Balah area and to analyse the most suitable location for applying the early warning systems at, Kuala Balah area. The study area for this research is Kuala Balah in the district of Jeli, Kelantan. The methodology used in conducting this study includes data collection which encompasses of the information from survey, interview and questionnaire that was distributed about ten per cent of the ﬂood victim’s populations and also the data obtained from the govemment department. The data is further proceeding with analysing and interpretation data to produce graph by using Microsoft excel and also Statistical Package for Social Sciences (SPSS). For early warning systems towards ﬂood, the result shows the maximum percentage which is 44% of the respondents that have selected for siren system which is represent about ll families in Kuala Balah that have faced massive ﬂood on 2014. Besides, based on the interview and responds from the villagers, the suitable locations to apply the systems have been determined. This because due to many loss of properties, places, livestock and also loss of life. Therefore, this study can be used in order to improve ﬂood mitigation process and ﬂood management for ﬁlture plan.